Analisis Daya Saing Ekspor Kakao Indonesia Ke Negara Mitra Perdagangan Utama Periode 2012 - 2021 - Fadillah, Fadillah; Wulandari, Siti Abir; Zainuddin, Zainuddin (Jurnal MeA (Media Agribisnis), 2024)
The purpose of this study was to determine the export development of Indonesian cocoa beans and cocoa powder on the international market in 2012-2021 and to analyze the development of export competitiveness of cocoa beans and cocoa powder. Indonesia in the international market in 2012-2021. In this research, the export destination of cocoa beans is to Malaysia, while the export destination of cocoa powder is to India, China, the Philippines and Malaysia. The analysis used in conducting this research is using Revealed Comparative Advantage (RCA), Export Competitive Index (ECI) and Trade Specialization Index (ISP). Based on research results. The average value of RCA, ECI and ISP exports to Malaysia in the 2012-2021 period is 2.79; 0.90 ; 0.48 > 0, which means that Indonesia has a comparative advantage, is competitive and is positioned as an exporter of cocoa beans to Malaysia. the research results for cocoa powder have an average RCA, ECI and ISP value of 14.38 respectively; 1.05 ; 0.99 to China, 18.09 ; 1.13 ; 1.00 to India , 11.22 ; 1.11 ; -0.27 to Malaysia, 5.72 ; 1.01 ; 1.00 to the Philippines which means that within the four countries Indonesia has a comparative, competitive advantage and is able to act as a cocoa powder exporting country, except for Malaysia where the ISP score of Indonesia is negative.